Survival skills: The impact of change and the ERA on Australian researchers - Hughes, Michael; Bennett, Dawn (Routledge, 2013)
This paper reports findings from a study that focused on the experiences of research-intensive academics in relation to the Excellence in Research for Australia Framework. Interviews with academic staff at different career stages and across all academic faculties followed completion of a short survey in which respondents compared their publishing behaviour before and since implementation of the new Framework. Respondents were highly conscious that ERA had prompted a shift in publishing behaviour to meet often-competing demands of individual research interests, institution, discipline, and the international research community. Indeed, the study revealed academics to be positioned in contradictory ways in relation to their research and publishing, heightened by the instability of the Framework’s assessment mechanisms. The experience of researchers up to and including the decision to abandon journal ranking provides valuable insights into the precarious and reactionary nature of academic research careers, and the ability of both individuals and institutions to negotiate the rapid rate of change. These insights include tension between personal research priorities and ERA requirements, particularly in relation to writing for the most relevant audience; and concerns about the right to exercise academic freedom.